The benefits of internationalization in higher Education. The experience in portuguese polytechnics. - Mourato, Joaquim (My University, 2019)
The European Commission [4] states that each Member State should adjust its national strategies to enhance its potential and international presence and attract talent. Account must be taken of both the national skills shortage and the lack of intercultural skills and the knowledge and research needs of their developing partner countries. Globalization is a process of great expansion, irreversible and with deep implications in all areas. This process will result in new opportunities and new challenges for the next generations of students and teachers looking to develop in an increasingly interdependent context. The Portuguese polytechnics, through the implementation of a concerted internationalization strategy between the institutions, have already achieved significant results in terms of international affiliations, international student and teacher and non-teaching staff mobility, joint programs and degrees and joint research projects. The internationalization of Portuguese higher education institutions (HEI) in recent years confirms the trend towards globalization of higher educa
Keywords: Internationalization; Higher education; Portuguese polytechnics; International cooperation